The Effectiveness of the Entrepreneurship MBKM Lecture Model: Alternatives to Improve Student Creativity Competencies during the Pandemic Covid-19 - Dwikoranto Dwikoranto (IKIP Mataram, 2022)
This study aims to produce an effective Entrepreneurship MBKM model in increasing student creativity by producing lecture outputs by students in the form of business plan drafts, startups, and entrepreneurship PkM proposals. The MBKM Entrepreneurship model used is said to be effective if there is an increase in creativity competence and it produces lecture outputs by students which are statistically significant and the average n-gain is at least in the moderate category. The research design in this study used a pre-experiment with a one group pre-test and post-test design. The research subjects were 30 students of Unesa physics in the 2021/2022 academic year. The instrument used in this research is a creativity assessment to assess student portfolio results. Data were analyzed using paired t-test and N-gain to see the increase in creativity. The results showed that there was a difference in creativity before and after the model was applied and a significant increase in student creativity and the average N-gain increase in student creativity in the medium criteria. In addition, students are able to produce creative products in the form of business plan drafts, startups, and entrepreneurship PkM proposals with a minimum score of B+.